Impacts of the COVID-19 pandemic on a human research islet program. Issue 1 (31st December 2022) - Dafoe, Tina J.; Dos Santos, Theodore; Spigelman, Aliya F.; Lyon, James; Smith, Nancy; Bautista, Austin; MacDonald, Patrick E.; Manning Fox, Jocelyn E.
ABSTRACT: Designated a pandemic in March 2020, the spread of severe acute respiratory syndrome virus 2 (SARS-CoV2), the virus responsible for coronavirus disease 2019 (COVID-19), led to new guidelines and restrictions being implemented for individuals, businesses, and societies in efforts to limit the impacts of COVID-19 on personal health and healthcare systems. Here we report the impacts of the COVID-19 pandemic on pancreas processing and islet isolation/distribution outcomes at the Alberta Diabetes Institute IsletCore, a facility specializing in the processing and distribution of human pancreatic islets for research. While the number of organs processed was significantly reduced, organ quality and the function of cellular outputs were minimally impacted during the pandemic when compared to an equivalent period immediately prior. Despite the maintained quality of isolated islets, feedback from recipient groups was more negative. Our findings suggest this is likely due to disrupted distribution which led to increased transit times to recipient labs, particularly those overseas. Thus, to improve overall outcomes in a climate of limited research islet supply, prioritization of tissue recipients based on likely tissue transit times may be needed. Graphical abstract: uf0001